2011
DOI: 10.1186/1475-2891-10-3
|View full text |Cite|
|
Sign up to set email alerts
|

The role of salt abuse on risk for hypercalciuria

Abstract: BackgroundElevated sodium excretion in urine resulting from excessive sodium intake can lead to hypercalciuria and contribute to the formation of urinary stones. The aim of this study was to evaluate salt intake in patients with urinary lithiasis and idiopathic hypercalciuria (IH).MethodsBetween August 2007 and June 2008, 105 lithiasic patients were distributed into 2 groups: Group 1 (n = 55): patients with IH (urinary calcium excretion > 250 mg in women and 300 mg in men with normal serum calcium); Group 2 (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
1
18
1
3
Order By: Relevance
“…This results contradicted with a study of [33] who reported that a relationship between higher fresh fruit intake and decreased risk of incident kidney stone formation type was less than 0.001 was which was considered statistically significant.…”
Section: Dietary Habits Among Patients With Kidney Stonescontrasting
confidence: 89%
“…This results contradicted with a study of [33] who reported that a relationship between higher fresh fruit intake and decreased risk of incident kidney stone formation type was less than 0.001 was which was considered statistically significant.…”
Section: Dietary Habits Among Patients With Kidney Stonescontrasting
confidence: 89%
“…The relationship between sodium intake and increased urinary calcium excretion is well established 20 . In another study, dietary salt intake was significantly higher in patients with idiopathic hypercalciuria 9 .…”
Section: Discussionmentioning
confidence: 88%
“…All patients were also instructed to maintain a protein intake of 0.8 to 1 g/kg body weight/ day and an adequate calcium intake (800 to 1000 mg/ day) 8 . Salt restriction (less than 5 g/ day) was recommended if appropriate based on their 24h urine sodium excretion 9 .…”
Section: Dietary Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…En relación al análisis de los factores de riesgo según el pH urinario, coincidimos con otro estudio (21), en que los pacientes con pH de orina en rango 5.5-7 presentan unos niveles de citrato más bajos, y por tanto más riesgo litógeno en relación a este factor metabólico. Tras el análisis de correlación lineal que observamos en la tabla 4, vemos que existen múltiples relaciones significativas, quizá la más interesante es la relación lineal positiva y significativa entre los niveles de sodio y de calcio en orina, lo que indica que a mayor excreción en orina de sodio, aumenta la calciuria, resultados que corroboran lo ya observado en otros estudios que indican que la mayor ingesta de sal aumenta el riesgo de hipercalciuria (22). Otro aspecto destacable del estudio es que las mujeres, aunque presentan menores factores de riesgo litógeno en orina, tienen un mayor porcentaje de hipovitaminosis D con respecto a los hombres, estando este factor de forma global más presente en pacientes formadores habituales de litiasis (23,24), aunque no se ha aclarado todavía cuál es su papel real en la fisiopatología de la litiasis urinaria.…”
Section: Discussionunclassified